2022
DOI: 10.1186/s42269-022-00708-0
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and analgesic activities of black cumin (BC, Nigella sativa L.) extracts in in vivo model systems

Abstract: Background Black cumin (Nigella sativa) is a widely used ingredient of traditional medicine for its broad-spectrum pharmacological actions, including analgesic, bronchial asthma, anti-inflammatory properties, and others. We sought to evaluate BC extracts' efficacy for the anti-inflammatory and analgesic properties using a comprehensive in vivo and in silico experimental setup. To investigate whether BC extract has anti-inflammatory and analgesic therapeutic potentials in vivo anti-inflammatory … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Additionally, NS may protect against neurodegenerative conditions such as Alzheimer's [15] and Parkinson's disease [16]. Pertinent to the present study, NS has repetitively exhibited anti-oxidative and anti-inflammatory properties [17][18][19][20][21], reducing the symptoms of headaches, menstrual cramps, and arthritis [22] and boosting immunity [23,24]. Several studies reported NS, and its active component thymoquinone, to reduce levels of pro-inflammatory cytokines including interleukin (IL)-6 and tumor necrosis factor (TNF)-α [3,[25][26][27][28][29].…”
Section: Introductionsupporting
confidence: 61%
“…Additionally, NS may protect against neurodegenerative conditions such as Alzheimer's [15] and Parkinson's disease [16]. Pertinent to the present study, NS has repetitively exhibited anti-oxidative and anti-inflammatory properties [17][18][19][20][21], reducing the symptoms of headaches, menstrual cramps, and arthritis [22] and boosting immunity [23,24]. Several studies reported NS, and its active component thymoquinone, to reduce levels of pro-inflammatory cytokines including interleukin (IL)-6 and tumor necrosis factor (TNF)-α [3,[25][26][27][28][29].…”
Section: Introductionsupporting
confidence: 61%
“…For headache and body pain, seeds of Nigella sativa, cloves of Allium sativum, and leaves of Centella asiatica are crushed together to obtain juice, which is then massaged onto painful areas. Analgesic and anti-inflammatory activities of Nigella sativa (black cumin) seeds have been demonstrated in acetic acid-induced writhing tests and carrageenan-induced rat paw edema [57] . A constituent of the seeds, thymoquinone, has been shown responsible for these two effects among others [58] .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, NSE markedly inhibited inflammation and hepatocyte apoptosis via PPARγ influenced modulation of JAK2/STAT3 and Bcl-2/Bax/Caspase-9 signaling pathways, suggesting a possible hepatoprotective role of NSE. NSE, rich in polyphenols such as quercetin, gallic acid, chlorogenic acid, m-coumeric acid, ferulic acid and sinapic acid, has been recognized for antioxidative [37,38], analgesic [39], anti-inflammatory, immunomodulatory [16,19] and anticancer [40] activities. Therefore, NSE was tested for its hepatoprotective effectiveness in this study.…”
Section: Discussionmentioning
confidence: 99%